DESA ADAT PROVINCIAL LAW: EXISTENCE STRENGTENING OR POWER FLEXING? - Apriani, Luh Rina; Erliyana, Anna (UI Scholars Hub, 2020)
The Desa Law gave rise to a discussion about the legitimacy of Desa Adat in Indonesia. Along with the main objective of the Desa Law to empower villages, some regions thought the normalization of Article 5 of the Desa Law would go hand in hand with the strengthening of the Desa Adat. The Siak Regency Government issued the Siak Regency Regulation No. 2 of 2018 concerning the Establishment of Desa Adat in Siak Regency, to compel the villages in their area to meet the criteria as Indigenous Villages as mandated by the Desa Law. The Regional Regulation of the Province of West Sumatra Number 7 of 2018 concerning Nagari shows political debate to fulfill the mandate of the Village Law, which is criticized as large among the minimal nuances of custom and culture. Bali, which has been living in a circle of the existence of Desa Adat and Desa Dinas, has also examined the responses to the existence of the Desa Law drawn from discussions and discourses on village integration and/or village elections. In the midst of this process, the Provincial Law of Bali Province No. 4 of 2019 was published in the Adat Law (Perda Desa Adat). This paper will show that the Desa Adat Law, which is rich in nuances of customs and culture, was not published to fulfill the mandate of the Desa Law, but instead strengthened the existence of Desa Adat in Bali. This Perda has revised traditional and official relations in Bali by giving more space to the Customary Villages to work together with the Dinas Desa in synergy to empower the community within the philosophical framework of the Balinese people. The effectiveness of this regional regulation needs to be tested to prove the authority of the Desa Adat and Desa Dinas in Bali.